Diseño de un centro comunitario integral ecológico para la Cooperativa 5 de junio, en el cantón Durán - Párraga Vélez, Diego Paúl (2023)
The implementation of adequate public facilities is essential for the development of a prosperous and equitable community. These facilities include parks, community centers, sports facilities and recreational spaces, promoting social interaction, well-being and community cohesion. In Duran and other growing cities, there are many underutilized public spaces, such as plazas, parks, community centers, schools, hospitals, streets, and green areas. These spaces, often relegated to marginal or disused areas, are perceived as dangerous or worthless. However, with the right attention and resources, they can be transformed into vibrant places for the community...........